KENAKALAN REMAJA DI WARNET BnB GAME CENTER KELURAHAN TUAH KARYA KECAMATAN TAMPAN KOTA PEKANBARU - Prasetyo, Dede; Hidir, Achmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Juvenile delinquency at the Bnb internet cafe game center in Pekanbaru city. This research was carried out in the city of pekanbaru further at Bnb internet cafe game center, Tuah Karya Sub-District, Tampan District. The purpose of this study was to find out what kinds of juvenile delinquency in the Bnb internet cafe game center were to find out the whole factors that caused adolescents to commit delinquency. The subjects in this study is 5 teenagers, who were 12-18 years old who were met in internet cafes who were addicted to playing online games. The author uses qualitative methods and the data is analyzed qualitatively and uses observational data collection techniques which include documentation and interviews. From the results of the research conducted the authors found that the 5 informants had the same hobby of playing online games to addiction and they were also smokers which resulted in them doing other delinquents such as skipping school, stealing and extortion. It can be concluded that the very basic factors that cause teenagers to do delinquency are invitations and incitements from their playmates. As well as several other causative factors, namely parents who are indifferent or not paying attention to their children, weak self-control that causes the teenagers easily influenced by the invitation of friends and the surrounding environment, and the mass media that have brought them into a new cultural pattern and mindset of teenagers.        Keywords:Mischief,Teenager